Are There Hallmarks of Child Abuse? II. Non-Osseous Injuries - Kepron, Charis (Acad Forensic Pathol, 2016)
Certain conditions have been considered hallmarks of child abuse. Such pathognomonic conditions have led to an inevitable diagnosis of inflicted injury. Forensic pathologists are faced with complex analyses and decisions related to what is and what is not child abuse. In this review, we examine the literature on the specificity of five conditions that have been linked to inflicted injury to varying degrees of certainty. The conditions examined include tears of the labial frena (frenula), cigarette burns, pulmonary hemorrhage and intraalveolar hemosiderin-laden macrophages as markers of upper airway obstruction, intraabdominal injuries, and anogenital injuries and postmortem changes. Analysis of the literature indicates that frena tears are not uniquely an inflicted injury. Cigarette burns are highly indicative of child abuse, though isolated cigarette burns may be accidental. Pulmonary hemorrhage is seen more commonly in cases with a history suggestive of upper airway obstruction, but is not diagnostic in an individual case. Hemosiderin-laden macrophages may be seen in cases with inflicted injuries and in natural deaths. Abdominal injuries may be seen in accidents and from resuscitation, though panreatico-duodenal complex injuries in children under five years of age are not reported to be seen in falls or resuscitation. The understanding of anogenital injuries is increasing, but misunderstanding of postmortem changes has led to miscarriages of justice.